Specific aspects of the radiographic morphometric and densitometric characteristics of mandible of the rats with experimental diabetes mellitus after tooth extraction - A. V. Abramov; K. S. Hanchev; Ye. V. Kadzharian (Patologìâ)
Diabetes mellitus is regarded today as a metabolic disease, which is considered to be a modulator of endodontic infections, is responsible for altering the immune and inflammatory responses, impedes the healing process, and contributes to damage of organs and tissues of the body, including tooth pulp and periapical tissues. The aim of the work is to study the radiographic characteristics of the dental septum of the alveolar crest of the mandible, crown and root of the low molars of rats with experimental streptozotocin diabetes at different times of the post-extraction period (the 1st, 7th and 14th day). Materials and methods. Studies were conducted on 120 male Wistar rats, 8–10 months old, divided into eight groups of 15 animals each. The experimental diabetes mellitus was modelled in 45 animals by a single administration of streptozotocin interperitoneally (SIGMA Chemical, the USA) at a dose of 50 mg/kg, diluted in 0.5 ml of 0.1 M citrate buffer (pH 4.5) ex tempore, on the 21st day after its induction the level of fasting glucose was determined (by the glucose oxidise method using standard test strips Test Strip II, glucometer Glucocard, Japan), which was 24.7 ± 2.2 mM/l. The extraction of the first low molar of the right mandible was realised using thiopental anaesthesia (40 mg / kg dose) with additional local infiltration anaesthesia with Ubistesine (3M Deutschland GmbH, Germany).On the 1st, 7th, and 14th day, dates that correspond to the experiment after the extraction of the tooth, the rats were decapitated using thiopental anaesthesia (dose 40 mg/kg).The visiography of the mandible was performed using a computerized 3D CBCT tomograph Panoura 18S Panoramic 3D. With the help of digital image analysis the radiographic density of tissues of the alveolar socket of the removed 1st molar, crown of the 1st, 2nd and 3rd molars, their root and dental septum of the alveolar crest were determined.